(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the growth and yield of radishes in response to cotton residue doses and biostimulant application. The experimental design was in randomized blocks in a 5 x 2 factorial scheme using the doses of 0; 25; 50; 75; 100 t ha-1 of cotton residue with or without biostimulant, with three replicates. At 32 days after emergency, the following variables were determined: plant height, leaf area, diameter of commercial roots, diameter of non-commercial roots, fresh mass of commercial roots, fresh mass of non-commercial roots, root dry mass, and dry mass of the plant leaves. Increases ranging from 49.74 to 1.291% were observed depending on the analyzed variable in comparing the control with the highest residue dose of 100 t ha-1. The biostimulant application treatments were up to 25.75% superior in relation to the treatments without application. It is concluded that cotton residue application and biostimulant are good alternatives to improve the performance of radish plants and can be used in organic production systems.